On the Value of Alert Systems and Gentle Rule Enforcement in Addressing Pandemics - Roth, Yefim; Plonsky, Ori; Shalev, Edith; Erev, Ido (Frontiers in Psychology, 2020)
The recent COVID-19 pandemic poses a challenge to policy makers on how to make the population adhere to the social distancing and personal protection rules. The current research compares two ways by which tracking smartphone applications can be used to reduce the frequency of reckless behaviors that spread pandemics. The first involves the addition of alerts that increase the users’ benefit from responsible behavior. The second involves the addition of a rule enforcement mechanism that reduces the users’ benefit from reckless behavior. The effectiveness of the two additions is examined in an experimental study that focuses on an environment in which both additions are expected to be effective under the assumptions that the agents are expected-value maximizers, risk averse, behave in accordance with cumulative prospect theory (Tversky & Kahneman, 1992), or behave in accordance with the Cognitive Hierarchy model (Camerer, Ho & Chong, 2004). The results reveal a substantial advantage to the enforcement application. Indeed, the alerts addition was completely ineffective. The findings align with the small samples hypothesis, suggesting that decision makers tend to select the options that led to the best payoff in a small sample of similar past experiences. In the current context the tendency to rely on a small sample appears to be more consequential than other deviations from rational choice.